Study on the Novels of R. K Narayan: with Special Reference to the Novel The Guide and the The Man-Eater of Malgudi: Exploring the Tragicomic Elements in R.K. Narayan's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2013)
R.K Narayan is a renowned Indian author. This paper presents R.K. Narayan as a tragicomic essayist. He features numerous comic and heartbreaking elements in his books. I have picked four of his books to present him as a tragi-comic essayist. They are The Guide, The English Teacher, The Financial Expert and The Man-Eater of Malgudi. R.K. Narayan. In these books, R.K. Narayan gives much significance to human connections and their results. Especially, he focuses on adoration, cash, and magnificence and shows how these outer and internal things influence our lives. He is without a doubt the master of comic composition, and he even demonstrates a genuine subject amusingly in a portion of his books like The Guide, The Financial Expert, and The Man-Eater of Malgudi. Be that as it may, in these books there is a fundamental sadness, which the perusers can undoubtedly understand truth be told, The English teacher is viewed as the best shocking novel of his vocation. In this way, he is successful both as a comic and disastrous author. The perusers can learn numerous exercises by perusing R.K. Narayan's books, and it very well may be comprehended through the finding of comic and shocking elements. The exposition attempts to clarify these things.